2016
DOI: 10.1590/1980-5373-mr-2015-0694
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Gold Nanoparticles Using Sumac Aqueous Extract and Their Antioxidant Activity

Abstract: Green synthesis of nanoparticles which have eco-friendly favourable solvent systems and environmentally reducing agents is of excessive importance. In this paper, we aimed to develop environmentally friendly, rapid and simple producer for the synthesis gold nanoparticles (Au-NPs) using aqueous extract of sumac as reducing agents for gold ions as well capping agent for the bioformed Au-NPs. The bio-synthesized Au-NPs were characterized by the UV-visible spectroscopy, FTIR, TEM, and zeta-potential measurements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 32 publications
6
47
0
Order By: Relevance
“…In Figure (a), the presence of a peak at 538 nm attributed to Au surface plasmon resonance (SPR) confirmed AuNPs formation. This result correlates with other reported work based on plant extracts; 530 nm ( Sumac ), 546 nm ( Garcinia mangostana fruit peel), 535 nm ( Amaranthus spinosus leaf extract), 530 nm (Aqueous extracts of Lamiaceae plants) . A broad shoulder peak was also observed at around 651 nm.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In Figure (a), the presence of a peak at 538 nm attributed to Au surface plasmon resonance (SPR) confirmed AuNPs formation. This result correlates with other reported work based on plant extracts; 530 nm ( Sumac ), 546 nm ( Garcinia mangostana fruit peel), 535 nm ( Amaranthus spinosus leaf extract), 530 nm (Aqueous extracts of Lamiaceae plants) . A broad shoulder peak was also observed at around 651 nm.…”
Section: Resultssupporting
confidence: 92%
“…[25] The absorption spectra of the as -synthesized AuNPs and Crinum macowanii bulb extract are shown in Figure 2. In Figure 2 with other reported work based on plant extracts; 530 nm (Sumac), [23] 546 nm (Garcinia mangostana fruit peel), [26] 535 nm (Amaranthus spinosus leaf extract), [24] 530 nm (Aqueous extracts of Lamiaceae plants). [25] A broad shoulder peak was also observed at around 651 nm.…”
Section: Uv-visible Light Spectroscopymentioning
confidence: 53%
See 1 more Smart Citation
“…3 In addition, molecular components of plant extracts have great affinity for the surface of nano-structures, and stabilize and prevent aggregation while improving the biological effects of NPs. 4 Thus far, more than 200 plants have been screened for their potential to produce inorganic NPs. 5,6 Dovepress Dovepress 8842 azizi et al developed palladium nanoparticles (PdNPs) that had remarkable optical, electronic, and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…1(d) and (e)) and revealed that the reaction time of 10 min for the aqueous Djulis shell extract is suitable for rapid prototyping and scaling up the process for practical applications. 5 Previous studies have reported that Au NPs were completely formed after a longer reaction than that noted for the Djulis shell extract, such as 25 min for Crescentia cujete L., 23 30-40 min for black cardamom, 24 1 h for Sumac, 25 and 24 h for Momordica cochinchinensis rhizome. 4 Furthermore, the Au NPs solutions of 744 and 930 μg mL −1 were stable at 4 ∘ C for at least 2 months.…”
Section: Characterization Of Au Npsmentioning
confidence: 92%